Barriers and Facilitates of Research Utilization as Perceived by Nurses of Suez Canal University Hospital-Ismailia-Egypt - Naglaa Ibrahim Mohamed; Maha Moussa Mohamed Moussa; Mirella Youssef Tawfik (Kufa Journal for Nursing Sciences)
Background: The goal of conducting healthcare related researches is to improve the delivery of healthcare services by implementing their evidences into practice. Our knowledge with regard to those factors that promote or discourage research utilization among nurses in clinical practice is limited.